Towards a theology of conflict solution: Understanding religious conflict in contemporary Nigerian society - A.O. Afolaranmi (Acta Theologica)
Adebayo Ola Afolaranmi writes a bookreview of: Akanji, I.A., (Abuja: Elis Associates, 2021), 595 pages, Price: 5000 Nigerian Naira, ISBN: 978-978-993-478-2 (paperback).